Adaptation and validation of the scale of perceived social support from vaux - Nava Quiroz, Carlos Narciso (2015)
The objective of this research was the adaptation to the Spanish language and statistical validation of Scale of Perceived Social Support (SPSS). This scale was chosen because by its metric properties and adequacy in the construction. Its theoretical structure is consistent with the type of findings and research on the international area. The analysis of the results showed some differences with regard to the English version -less items in our study- probably due to cultural contrasts. However, another type of variables cannot be ruled out. The relative value of this adaptation may be evaluated by empirical studies that realize the construct of social support as defined, and in agreement with the theoretical framework for construction of the scale in question.